Radiological study of anorectal malformations - Marta, Hernán; Chavarría, Oscar; Falco de Torres, Editta (Cirugía del Uruguay, 1979)
Radiologic study of ano - rectar malformations should aim at establishing lesional level with respect tci puborectal bundle of levator ani and early detection of associated malformations.